Blind Sailors' Spatial Representation Using an On-Board Force Feedback Arm: Two Case Studies. (5th December 2013) - Simonnet, Mathieu; Ryall, Eamonn
Abstract : Using a vocal, auditory, and haptic application designed for maritime navigation, blind sailors are able to set up and manage their voyages. However, investigation of the manner to present information remains a crucial issue to better understand spatial cognition and improve navigation without vision. In this study, we asked two participants to use SeaTouch on board and manage the ship headings during navigation in order to follow a predefined itinerary. Two conditions were tested. Firstly, blind sailors consulted the updated ship positions about the virtual map presented in an allocentric frame of reference (i.e., facing north). In the second case, they used the forced-feedback device in an egocentric frame of reference (i.e., facing the ship headings). Spatial performance tended to show that the egocentric condition was better for controlling the course during displacement, whereas the allocentric condition was more efficient for building mental representation and remembering it after the navigation task.